PRECAF Randomized Controlled Trial. (January 2021) - Kuo, Ling; Frankel, David S.; Lin, Aung; Arkles, Jeffrey; Hyman, Matthew; Santangeli, Pasquale; Marchlinski, Francis E.; Nazarian, Saman
Abstract : Background: We have previously shown that the presence of dual muscular coronary sinus (CS) to left atrial (LA) connections, coupled with rate-dependent unidirectional block in one limb, is associated with atrial fibrillation (AF) induction. This study sought to examine whether ablation of distal CS to LA connections at a first AF ablation reduces arrhythmia recurrence during follow-up. Methods: In this single-center, randomized, controlled trial, 35 consecutive patients with drug-refractory AF undergoing first-time ablation between August 2018 and August 2019, were randomly assigned to (1) standard ablation (pulmonary vein isolation and nonpulmonary vein trigger ablation) versus (2) standard ablation plus elimination of distal CS to LA connections targeting the earliest LA activation during distal CS pacing with a deca-polar catheter placed with its proximal electrode at the ostium. Change of the local CS atrial electrogram and LA activation sequence to early activation of the LA septum or roof during distal CS pacing were the end point for CS-LA connection elimination. Results: Thirty patients completed 6 months study follow-up (15 patients in each group). Demographic characteristics including age and AF persistence were similar in both groups. After a mean follow-up of 170±22 days, there were 7 atrial arrhythmia recurrences in the standard group and 1 recurrence in the CS-LA connection elimination group (46.7% versus 6.7%, hazard ratio, 0.12, P =0.047). Conclusions: Elimination of distal CS to LA connections reduced atrial arrhythmia recurrences compared with standard pulmonary vein isolation and nonpulmonary vein trigger ablation in patients undergoing a first AF ablation procedure in a small randomized study. This strategy warrants further evaluation in a multicenter randomized trial. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03646643.